Draft sur les organisations du domaine de la santé dans le système sanitaire au Burkina Faso - Banhoro, Yacouba (Globalization and health policy in West Africa, 2023)
This draft deals with the legal framework for health policies in Burkina Faso.
Keywords: World health; Health; West Africa; Health Organisation; Typology; Legal Framework; Categorisation; Global Health Policy; Burkina Faso